Respiratory Microbiome of New-born Infants - David John Gallacher; Sailesh eKotecha (Frontiers Media S.A., 2016)
The respiratory tract, once believed to be sterile, harbours diverse bacterial communities. The role of microorganisms within health and disease is slowly being unravelled. Evidence points to the neonatal period as a critical time for establishing stable bacterial communities and influencing immune responses important for long term respiratory health. This review summarises the evidence of early airway and lung bacterial colonisation and the role the microbiome has on respiratory health in the short and long term. The challenges of neonatal respiratory microbiome studies and future research directions are also discussed.